The synergy between ionizing radiation and immunotherapy in the treatment of prostate cancer. (September 2017) - Sathianathen, Niranjan J; Krishna, Suprita; Konety, Badrinath R; Griffith, Thomas S
There has been a surge in the use of immunotherapy for genitourinary malignancies. Immunotherapy is an established treatment for metastatic renal cell carcinoma and nonmuscle invasive bladder cancer, but its potential for treating prostate cancer (PCa) remains under investigation. Despite reported survival benefits, no published Phase III PCa trials using immunotherapy only as a treatment has demonstrated direct antitumor effects by reducing prostate-specific antigen levels. Subsequently, the thought of combining immunotherapy with other treatment modalities has gained traction as a way to achieving optimal results. Based on data from other malignancies, it is hypothesized that radiotherapy and immunotherapy can act synergistically to improve outcomes. We will discuss the clinical potential of combining immune-based treatments with radiotherapy as a treatment for advanced PCa.